Determination of Quality and Trophic Status of Cibabat Lake, Cimahi City - Eka Wardhani; Tri Rizki Nopiyani; Dian Noor Handiani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
In Cimahi City, the river water is heavily polluted, and well water is not suitable for drinking water, so to anticipate the lack of clean water, the Environmental Service is planning to revitalize one of the ponds, namely the Cibabat Lake. This study’s purpose is to determine the reservoir’s condition based on water quality and trophic status. The method used for calculating water quality status is the Pollutant Index, which refers to the Decree of the Minister of Environment Number 115 of 2003 with results is 8,450, and will be 8,751 in 2022, with the water quality classified status as moderately polluted. Meanwhile, the method to assess trophic status uses the Carlson Trophic State Index (TSI) method by taking air samples for the parameters Total Nitrogen, Total Phosphate, Chlorophyll-a, and brightness which is included in the hypereutrophic category. The Cibabat Reservoir has been polluted by domestic waste based on the calculation of the potential pollutant load such as BOD, COD, TSS, Total Phosphate and Total Nitrogen in the border area is 2,219,600; 3,051,950; 2,108,620; 11,623; and 108,206 kg/day, respectively. DTA area is 1,886.660: 2,594.158; 1,792.327; 9,905; 91.975 kg/day, respectively. This is influenced by the increasing population each year.